Experimental Determination of the Absorption Cross-Section and Molar Extinction Coefficient of Colloidal CdSe Nanoplatelets - Yeltik, Aydan (2016)
There has been a strong interest in solution-processed two-dimensional nanomaterials because of their great potential in optoelectronics. Here, the absorption cross-section and molar extinction coefficient of four and five monolayer thick colloidal CdSe nanoplatelets (NPLs) having various lateral sizes are reported. The absorption cross-section of these NPLs and their corresponding molar extinction coefficients are found to strongly depend on the lateral area. An excellent agreement is observed between the experimental results and the calculated values based on the small-particle light absorption model. With these optical properties, NPLs hold great promise for optoelectronic applications.